SCIENTIFIC ATTITUDE AND THEIR RELATIONSHIP WITH STUDENTS' SCIENCE LITERACY IN JUNIOR HIGH SCHOOL - Arsyad, Arsyad; Safitriani, Safitriani (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Current education emphasizes the development of scientific attitudes such as curiosity, objectivity, and critical thinking as provisions for facing global challenges. These scientific attitudes play an important role in improving the scientific literacy of junior high school students because they encourage an understanding of science as a process of thinking and evidence-based investigation. This study aims to provide an overview of the profile of the scientific attitude ability and scientific literacy ability of students in Junior High School. The approach used in this research is quantitative with the sampling technique being total sampling. Based on the data that has been obtained, followed by the discussion described above, at the end of the study it can be concluded that the profile of the scientific attitude ability and scientific literacy ability of students in Junior High School, is dominated by students (students) with the ability of scientific attitudes with the category "good" as much as 38.16%, the "very good" category as much as 30.26%, the "medium" category as much as 22.37%, and as much as 9.21% for the "low" category. As for science literacy ability, it is dominated by students with the ability in the "good" category as much as 35.53%, the ability in the "very good" category as much as 32.89%, the "moderate" category as much as 21.05%, and the remaining 10.53 % categorized as “low”. Based on the results of the correlation test, it can also be concluded that there is a significant correlation between the ability of scientific attitudes and the ability of students' scientific literacy. Therefore, it shows that the ability of scientific attitudes has a significant effect on students' scientific literacy skills. ABSTRAK Pendidikan saat ini menekankan pengembangan sikap ilmiah seperti rasa ingin tahu, objektivitas, dan berpikir kritis sebagai bekal menghadapi tantangan global. Sikap ilmiah ini berperan penting dalam meningkatkan literasi ilmiah siswa SMP karena mendorong pemahaman sains sebagai proses berpikir dan penyelidikan berbasis bukti. Penelitian ini bertujuan untuk memberikan gambaran tentang profil kemampuan sikap ilmiah dan kemampuan literasi sains siswa SMP. Pendekatan yang digunakan dalam penelitian ini adalah kuantitatif dengan teknik pengambilan sampel adalah total sampling. Berdasarkan data yang telah diperoleh, dilanjutkan dengan pembahasan yang telah diuraikan di atas, pada akhir penelitian dapat disimpulkan bahwa profil kemampuan sikap ilmiah dan kemampuan literasi sains siswa SMP, didominasi oleh siswa (peserta didik) dengan kemampuan sikap ilmiah dengan kategori “baik” sebanyak 38,16%, kategori “sangat baik” sebanyak 30,26%, kategori “sedang” sebanyak 22,37%, dan sebanyak 9,21% untuk kategori “rendah”. Sedangkan untuk kemampuan literasi sains didominasi oleh siswa dengan kemampuan pada kategori “baik” sebanyak 35,53%, kemampuan pada kategori “sangat baik” sebanyak 32,89%, kategori “sedang” sebanyak 21,05%, dan sisanya sebesar 10,53% berkategori “rendah”. Berdasarkan hasil uji korelasi juga dapat disimpulkan bahwa terdapat korelasi yang signifikan antara kemampuan sikap ilmiah dengan kemampuan literasi sains siswa. Dengan demikian, hal tersebut menunjukkan bahwa kemampuan sikap ilmiah berpengaruh signifikan terhadap kemampuan literasi sains siswa.